Psychological Workplace Relationships as Strategic Drivers of Organizational Performance - Adi Purwanto (International Forum of Researchers and Lecturers, 2026)
Organizational performance increasingly depends on leadership practices that create psychologically supportive workplace relationships. Although Inclusive Leadership has been recognized as an important factor in improving employee engagement, collaboration, innovation, and organizational performance, previous studies have mainly emphasized Psychological Safety as the primary explanatory mechanism. This study aims to examine the mediating role of Psychological Workplace Relationships in the relationship between Inclusive Leadership and Organizational Performance. This study employed a quantitative explanatory research design using a cross-sectional survey involving academic and administrative staff at Universitas Ngudi Waluyo, Indonesia. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the measurement model, structural relationships, and mediation effects. The results indicate that Inclusive Leadership significantly improves Psychological Workplace Relationships by strengthening openness, accessibility, fairness, trust, and supportive communication. Furthermore, Psychological Workplace Relationships positively influence Organizational Performance through enhanced collaboration, knowledge sharing, employee engagement, adaptability, and innovative behavior. The findings also confirm that Psychological Workplace Relationships significantly mediate the relationship between Inclusive Leadership and Organizational Performance. This study expands the Inclusive Leadership literature by introducing Psychological Workplace Relationships as a broader relational mechanism beyond Psychological Safety. By integrating trust, respect, emotional support, and open communication, this research provides a comprehensive explanation of how inclusive leadership contributes to sustainable organizational effectiveness and offers practical implications for developing supportive workplace environments.